Still an Issue: The Use of Electronic Books in University Libraries in Nigeria - Esoname, Subair, Roselyn; Daniel, Oriogu, Chuks (American Journal of Social Sciences and Humanities, 2016)
The advent of information and communication technology has greatly provided an enabling means of electronic version of book that is vital to today users educational pursuit. Therefore, this study review literature on the conceptual overview of e-book, growth, relevance, challenges to university libraries and opportunity for sustainability. Hence, to overcome the turbulence issue of discourse, university libraries should endeavour to provide technological facilities that will facilitate effective use of e-book. Therein publishers, aggregators, vendors and librarians should collaborate on a streamlined mutual congenial business models which will enable effective subscription platform stable for easy restitution.